Women in Medieval History and Historiography - Stuard, Susan Mosher (University of Pennsylvania Press, 2016)
What was the status of women in the Middle Ages? How have women fared in the hands of historians? And, what is the current state of research about women in the Middle Ages? Susan Mosher Stuard and contributors address these questions.
Keywords: Women -- History -- Middle Ages, 500-1500.; Social history -- Medieval, 500-1500.; Women historians.; Femmes -- Histoire -- 500-1500 (Moyen Âge); Histoire sociale -- 500-1500 (Moyen Âge); Historiennes.; historians.; HISTORY -- Historiography.; Social history -- Medieval; Women historians; Women -- Middle Ages; 500-1500; Electronic books.; History